Voluntary and involuntary termination: Legal, ethical, and organizational implications in managing employee separation - Xuan, Pang Chia; Ismail, Fadillah (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates Malaysian termination policies from legal, ethical, and organizational perspectives. Regarding the terms under the Employment Act 1955 and Industrial Relations Act 1967, terminations often generate conflicting interests between businesses and employees. Usually linked to a change in employment or retirement, voluntary terminations which often follow a legal process may cause operations to be hampered but leave less legal documentation. On the other hand, terminations are found to be forced and based on duplicity or misconduct; this naturally indicates insufficient procedural justice during the termination process as evidenced in Ng Chang Seng Seng v Technip Geoproductions. This study adopts a legal analysis approach and case literature review to assess the impact of voluntary and involuntary terminations on workers’ rights in Malaysia. The study recommends reforms to the structure of severance benefits and increased access to career transition programs.